PENGARUH VARIASI PARAMETER WIRE-CUT EDM MITSUBISHI BA-8 TERHADAP KEKASARAN PERMUKAAN BAJA SKD 61 - Putratama, Panji Hastawirata; Jatisukamto, Gaguk; Sakura, Rahma Rei; HT Prasetiyo, Dani; Zainul M, Aris (Jurusan Teknik Mesin, 2024)
Wire-cut EDM is a machining process used to shape precision machine components. The basic principle of wire-cut EDM is the erosion of the workpiece through spark discharges in a dielectric fluid. The spark discharge is caused by a positive electrode approaching the negatively charged workpiece, creating a short circuit that generates heat energy. Previous research was conducted with factors such as current, wire speed, on-time, and variable frequency, resulting in the best surface roughness value of 6 µm. This study aims to determine the effect of parameters such as current, voltage, and wire speed on the response of surface roughness, using the Taguchi method. The workpiece used was SKD 61 steel with 600mm x 50mm x 5mm dimensions. Cutting was done at currents of 4, 6, and 9 (Amperes), voltages of 4, 5, and 6 (Volts), and wire speeds of 8, 10, and 12 (m/m). The results of this study showed the best surface roughness value of 2.540 µm with an S/N ratio of -8.09553 at a current of 4A, voltage of 4V, and wire speed of 8m/m. After optimization, a higher S/N ratio of -8.018 was achieved. Data analysis with ANOVA showed that the effect of factors on the response yielded an F-value greater than the F-table value for all factors, indicating that all factors had a significant impact. The percentage contribution of all factors was as follows: Current at 82.46%, Voltage at 3.36%, and Wire speed at 2.53%. Keywords: wire-cut EDM, taguchi method, surface roughness.